(untitled) (Journal of Asian Geography, 2023)
As an essential place for ecotourism, scientific research, and the educational environment, the national park is an essential part of the research conducted by many experts and scholars. To build an evaluation system of the sustainable development of national parks, and to deeply study the content of the sustainable development of national parks in China, to provide a new direction for the national parks in the sustainable development road of tourism. Studies have shown: 1. As the core content of national parks, the ecosystem is still the focus of experts and scholars, among which the authenticity and integrity of ecosystems account for the highest proportion. 2. According to the evaluation results of experts, it is concluded that China's national parks are currently in the basic sustainable development stage of tourism. There are more opportunities and space for the sustainable stage of future tourism development. 3. At present, China's national parks are representative of the ecosystem, the authenticity of the ecosystem reaches good coordination, and the suitability of the area and scale is moderately unbalanced. To study and explore the factors affecting the tourism sustainability of national parks and to provide a meaningful direction and reference basis for the protection and management of their formulation of policies and systems.